La vérité dans le sang : roman policier et connaissance - Marion François (Revue LISA)
The traditional detective novel is presented as the archetype of the literature of access to knowledge, the extreme point of the claim to telling the truth and giving sense by a tale which goes back meticulously and scientifically to the beginning : it is ratio which has the last word, in the assertion of the absolute autonomy of the rational process, which is posed as origin and unique finality, driving back the major interrogations of mankind behind what is presented in the form of an innocent game of chess. The contemporary form of the detective novel has re-modelled this vision considerably. What modern authors dispute, to different degrees, is traditional coincidence with a closed form, i.e. one which is completed, with a closed meaning and clearly formulated. For them, the experimentation on form goes along with that on significance, going through a modification of the relation to the meaning. The end will not always explain the beginning, so that the reader becomes aware that a question is always answered by another question, and that the first is only the start, in the spiral of generalized suspicion, of the questioning of original certainties.